Electrical Wing Prototype Anti Icing pada Pesawat Komersil - Elfitra Desifatma (Jurnal Jaring SainTek, 2020)
The accumulation of ice on the aircraft's wings can cause a decrease in the aerodynamic properties of the aircraft, increase in weight, and it is difficult to control the aircraft so that it affects aircraft safety. Icing handling on aircraft is growing. One of the newest systems being developed is electrical anti-icing. Therefore, the researcher designed a prototype of an anti-icing electrical wing on a commercial aircraft with advantages in terms of maintenance and lighter components. The purpose of making this prototype is to design an anti-icing electrical wing in the form of a prototype and can be used as an anti-icing. The prototype consists of three parts, namely input, control unit, and heating element. The heating element working system is by attaching the heating element to the surface of the wing, so when the tool is active through the controls, the heating element will work with an indication of the LED on. After testing the Prototype electrical anti-icing function that has been made, it can be used as a de-icing that removes icing that has already frozen on the leading edge.